1996
DOI: 10.1021/ja953843c
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Complexation between Bovine Serum Albumin and the Self-Assembled Hydrogel Nanoparticle of Hydrophobized Polysaccharides

Abstract: Macromolecular complexation between bovine serum albumin (BSA) and self-assembled hydrogel nanoparticle formed by the self-aggregation of cholesterol-bearing pullulan (CHP) was studied by high performance size exclusion column chromatography (HPSEC) and circular dichroism (CD). The CHP self-aggregates complexed with one BSA molecule to give colloidally stable nanoparticles (R G = 17 nm) at pH 7.0 and 25 °C. This was almost irrespective of the substitution degree of the cholesterol group of CHP. The helical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
153
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(154 citation statements)
references
References 31 publications
0
153
0
Order By: Relevance
“…Especially, the hydrophobic interaction between the hydrophobic domain and the hydrophobic surface of insulin exposed by part denaturation is very important, and is the main driving force for the denaturation of the insulin-FITC native structure. 19,24,[29][30][31][32] Possibly due to part denaturation, it was observed that the hydrophilic insulin-FITC molecules immediately became precipitate, when adding peptide RATEA16 into its aqueous solution (see Supporting Information). At the same time, the extent to b-sheet secondary structure of peptide increased, indicating that the existence of insulin-FITC molecules redounded to the b-sheet formation of peptide RATEA16.…”
Section: Drug Loadingmentioning
confidence: 99%
“…Especially, the hydrophobic interaction between the hydrophobic domain and the hydrophobic surface of insulin exposed by part denaturation is very important, and is the main driving force for the denaturation of the insulin-FITC native structure. 19,24,[29][30][31][32] Possibly due to part denaturation, it was observed that the hydrophilic insulin-FITC molecules immediately became precipitate, when adding peptide RATEA16 into its aqueous solution (see Supporting Information). At the same time, the extent to b-sheet secondary structure of peptide increased, indicating that the existence of insulin-FITC molecules redounded to the b-sheet formation of peptide RATEA16.…”
Section: Drug Loadingmentioning
confidence: 99%
“…Indeed, thermoresponsive hydrogel nanoparticles and mesoporous membranes have been reported. 8 However, it is difficult to construct mechanically robust macrostructures by using nanoparticles alone. Mesoporous membranes, on the other hand, show slow response due to the small pore size, but good retention of morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Various cholesterol-bearing pullulans with different MWs of the parent pullulan and DS of the cholesteryl moiety was synthesized (Nishikawa et al, 1996;Akiyoshi et al, 1997). Irrespective of the MW of the parent pullulan and the DS, all of cholesterol-pullulans provided unimodal and mono-disperse self-aggregates in water.…”
Section: Cyclic Hydrophobic Moleculesmentioning
confidence: 99%